The concept of LERNEN as a cognitive dominant of the educational discourse (based on the material of German language textbooks) - V.E. Shukman; S.I. Dubinin (Ученые записки Казанского университета: Серия Гуманитарные науки)
Comparative analysis of the specifics of representation of the concept of LERNEN as a cognitive dominant of the educational discourse in the modern German language textbooks of elementary level for foreigners was carried out. The aim of this research is to identify lexical elements marking the educational discourse of Germany and verbalizing the concept of LERNEN in the textbooks. In line with this aim, the following tasks were set: to reveal and categorize lexical elements representing the concept of LERNEN in all structural components of the selected textbooks; to quantify the revealed representatives and show their relations graphically; to perform both qualitative and comparative analysis of the representatives of the thematic groups of each textbook separately and in comparison with each other. The main method used during the research was conceptual analysis of the educational discourse on the basis of the textbooks of elementary level. The obtained results demonstrate that the representatives of the concept of LERNEN can be divided into 13 thematic groups. Their quantitative ratio was established on the basis of the textbooks. The thematic groups with a predominant number of representatives were determined. All lexical elements representing the concept of LERNEN were qualitatively investigated and their positions in the educational discourse were established. We found the ways of representing the concept of LERNEN as a large and crucial cognitive dominant and marking it with the help of the studied representatives associated with not only the modern educational discourse in the field of foreign languages learning, but also with the educational policy of Germany in general, which is highly relevant because of the high attraction and active influx of foreign students, tourists, and migrants to Germany. The results obtained are of great importance for further research of the cognitive basis of modern German language textbooks.